Efeitos da gestão de residuos de abate no crescimento inicial de Eucalyptus globulus Labill.: resultados de um estudo lisimétrico - Fabião, António (2009)
The effects of slash management on growth and nutrition of E. globulus seedlings were assessed through a lysimetric experiment. Treatments were removal of slash (R), broadcast on soil surface (S), and incorporation into the soil (I). Tree ggrowth and biomass, fine root dynamics, concentration of mineral N and base cations in soil solution, tree nutrition status (by root bioassays and foliar analysis), soil temperature and moisture were monitored.